Incremental value of Veterans Specific Activity Questionnaire and the YMCA-step test for the assessment of cardiorespiratory fitness in population-based studies. - Teren, A.; Zachariae, S.; Beutner, F.; Ubrich, R.; Sandri, M.; Engel, C.; Loffler, M.; Gielen, S. (Eur J Prev Cardiol, 2016)
BACKGROUND: Cardiorespiratory fitness is a well-established independent predictor of cardiovascular health. However, the relevance of alternative exercise and non-exercise tests for cardiorespiratory fitness assessment in large cohorts has not been studied in detail. We aimed to evaluate the YMCA-step test and the Veterans Specific Activity Questionnaire (VSAQ) for the estimation of cardiorespiratory fitness in the general population. METHODS: One hundred and five subjects answered the VSAQ, performed the YMCA-step test and a maximal cardiopulmonary exercise test (CPX) and gave BORG ratings for both exercise tests (BORGSTEP, BORGCPX). Correlations of peak oxygen uptake on a treadmill (VO2_PEAK) with VSAQ, BORGSTEP, one-minute, post-exercise heartbeat count, and peak oxygen uptake during the step test (VO2_STEP) were determined. Moreover, the incremental values of the questionnaire and the step test in addition to other fitness-related parameters were evaluated using block-wise hierarchical regression analysis. RESULTS: Eighty-six subjects completed the step test according to the protocol. For completers, correlations of VO2_PEAK with the age- and gender-adjusted VSAQ, heartbeat count and VO2_STEP were 0.67, 0.63 and 0.49, respectively. However, using hierarchical regression analysis, age, gender and body mass index already explained 68.8% of the variance of VO2_PEAK, while the additional benefit of VSAQ was rather low (3.4%). The inclusion of BORGSTEP, heartbeat count and VO2_STEP increased R(2) by a further 2.2%, 3.3% and 5.6%, respectively, yielding a total R(2) of 83.3%. CONCLUSIONS: Neither VSAQ nor the YMCA-step test contributes sufficiently to the assessment of cardiorespiratory fitness in population-based studies.
Keywords: Adult; Aged; Body Mass Index; *Cardiorespiratory Fitness; Cardiovascular Diseases/epidemiology/*prevention & control; Electrocardiography; Exercise/*physiology; Exercise Test; Female; Follow-Up Studies; Germany/epidemiology; Humans; Male; Middle Aged; Morbidity/trends; Oxygen Consumption; *Population Surveillance; Retrospective Studies; *Surveys and Questionnaires; Time Factors; *Veterans; Young Adult